KANDUNGAN MIKROBA PADA DAGING SAPI DARI BEBERAPA PASAR TRADISIONAL DI BANDAR LAMPUNG - Sugiyoto ,; Kusuma Adhianto; Veronica Wanniatie (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
This study aims to find out the microbial content contained in meat sold in traditional markets in Bandar Lampung. Survey method used in this study. Data collecting technique in this study were purposive sampling method and questionnaire method. Sampling was conducted on purpose in accordance with the requirements specified were: 1) the amount of meat sale > 25 kg / day, 2) one's own / work remains, 3) long to sell a minimum of 2 years. The amount of meat samples were taken as 200 grams from each trader. The number of trader which meat taken were 17 traders fro 8 markets. Sampling was conducted at 06.00 pm. The meat samples tested by bacteriological examination of Total Plate Count (TPC), the coliform and Salmonella sp. Research was conducted in the laboratory of Hall Veterinary Bandar Lampung. The result showed that 17, 65% of beef traders in traditional markets Bandar Lampung contained Total Plate Count (TPC) exceeds the standard, 58.82% of beef contains traders coliform above the standard and 35.29% beef trader in traditional markets in Bandar Lampung contained Salmonella sp. above the standard based SNI: 7388: 2009.